PIYAGĔM CIKĔRUH (1631 M): SIMBOL RELASI KUASA KERAJAAN MATARAM ISLAM DI PRIANGAN - Alnoza, Muhamad (Paradigma: Jurnal Kajian Budaya, 2025)
After the collapse of the Sunda Kingdom in the 16th century, most of its territory was controlled by the Islamic Mataram Kingdom. The occupation of Islamic Mataram in the ethnic Sundanese area in fact left behind several metal inscriptions known as piyagĕm. This study specifically examines the oldest piyagĕm found in the Priangan area, namely Piyagĕm Cikĕruh from Garut Regency. Based on the assumption that every inscription that is king is a symbol of power, this study focuses on science which is a symbol of power relations in Piyagĕm Cikĕruh. This study was conducted with the aim of finding the meaning of the symbols of the power relations. The results of this study are then downloaded that Piyagĕm Cikĕruh uses Islamic religious elements and Javanese-Sundanese cultural identity as symbols of power relations. These symbols are related to the meaning of the cultural hegemony of the Islamic Mataram Kingdom towards its rule in Priangan